Ecological characteristics and DNA barcoding of alien aphidoidea species included in the Black book of invasive animal species of Belarus - Varabyova, Maryia; Zhorov, Dmitrii (Journal of the Belarusian State University. Ecology, 2023)
The paper provides information on geographical and bio-ecological features of 10 invasive aphid species, which are pests of ornamental, fruit and agricultural crops. It is marked that according to trophic specialization most species (Brachycaudus (Acaudus) divaricatae Shaposhnikov, 1956, Panaphis juglandis (Goeze, 1778), Drepanosiphum platanoidis (Schrank, 1801), Phyllaphis fagi (Linnaeus, 1767), Hyadaphis tataricae (Aizenberg, 1935), Brevicoryne brassicae (Linnaeus, 1758), Cryptomyzus ribis (Linnaeus, 1758)) belongs to the highly specialized phytophages. Phyllobiont species (Pemphigus spyrothecae Passerini, 1856, P. juglandis, D. platanoidis, Ph. fagi, H. tataricae, C. ribis) predominate, belonging to the dendrobiont phytobiont group (P. spyrothecae, P. juglandis, D. platanoidis, Ph. fagi), whereas dendrochortobionts (B. divaricatae), dendrotamnobionts (Aphis spiraecola Patch, 1914), tamnobionts (H. tataricae), chortobionts (B. brassicae), tamnochortobionts (C. ribis) and dendrotamnochortobionts (A. craccivora) are represented by single species. Most alien invasive aphids (A. cassivora, A. spiraecola, B. divaricatae, B. brassicae, D. platanoidis, P. juglandis, Ph. fagi) are characterized by an open-living lifestyle, living in open galls is typical for 2 species (H. tataricae, C. ribis) and 1 adventive species initiates formation of closed galls (P. spyrothecae). Most species of aphids from the reentrant fauna of Belarus are noted to have the ability to initiate deformations of various plant parts, and 3 species (H. tataricae, C. ribis, P. spyrothecae) are characterized by the formation of open and closed galls. To date, the COI gene nucleotide sequences are available for 10 alien invasive aphid species for Belarus, including B. divaricatae, P. juglandis, and D. platanoidis, which have been decoded and deposited in the International Nucleotide Sequences Database (BOLDSystems). As part of this study, the nucleotide sequences of the COI gene of 5 aphid species of the recentral fauna of Belarus, among the alien invasive species (B. divaricatae, P. juglandis, D. platanoidis, A. spiraecola, A. caccivora) were decoded.
Keywords: invasive species; aphids; phytophagous; nucleotide sequence; COI gene; fauna